Comparative Study of Risk and Return in Bitcoin, LQ45, and Jakarta Islamic Index Markets in Indonesia (2021-2024) - Hidayat, Arif; Hanif; Heni Verawati (The Postgraduate of Institut Agama Islam Negeri Metro Lampung, 2025)
Introduction: In digital era, investments are no longer in the form of physical instruments or those we can see; there are many non-physical investment instruments, such as Cryptocurrencies and stocks. However, before we jump directly into the world of investment, we need to analyze how an investment instrument can bring our money into profit and consider the risks of investment instruments to avoid losses. Objective: This study examines the risks and returns of three investment instruments: Bitcoin, LQ45, and the Jakarta Islamic Index. Method: This study used a Descriptive quantitative approach and comparative analysis. To obtain data, we used purposeful sampling, a non-probability sampling technique. Forty-eight samples were examined using historical monthly closing price data for Bitcoin, LQ45, and the Jakarta Islamic Index from 2021 to 2024. Results: Research findings show that Bitcoin investment has the highest level of risk compared to LQ45 and Jakarta Islamic Index investments, then LQ45 investment has a moderate risk level, and Jakarta Islamic Index investment has the lowest level of risk compared to Bitcoin and LQ45 investments. In further findings, it is known that Bitcoin investment has the highest level of return compared to LQ45 and Jakarta Islamic Index investments, then LQ45 investment has a moderate level of return, and Jakarta Islamic Index investment has the lowest level of return compared to Bitcoin and LQ45 investments. Implications: Thanks to this research, investors should be able to evaluate and assess the risk and return of investing in Bitcoin, LQ45 shares, and Jakarta Islamic Index Sharia shares. Additionally, prior investors can distinguish investment portfolios based on their investment instruments' risk and return requirements.